Optimalisasi Pemanfaatan Sumberdaya Lahan untuk Pengembangan Tanaman Perkebunan - PUJA, I NYOMAN; ADNYANA, I MADE; ARTHAGAMA, DEWA MADE (Agrotrop : Journal on Agriculture Science; Vol 4 No 1 (2014), 2014)
Optimizing the Use of Land Resources for the Development of Crop Plantation. The population and food needs increase every year; on the other hand, the productive areas for agriculturedecreases. Therefore, reasearch concerning of the utilization of land resources for the development ofplantation crops was required to overcome this problem. The aim of the research was to investigatecrops plantation that was suitable for multiple cropping. This research was conducted by survey andlaboratory analysis, such as : preparation (making land units with overlay maps of slope, soil type andland use), field surveys, soil sample analysis, tabulation, interprestation of data, and matching betweenthe land characteristics and the factors of plants growth. Those matching will get the appropriateamount of plantation crop development. The results show that Arabica coffee was not suitable in thewhole area which is developed in Abang District. Cashew plant quite appropriate to be developedarea 1,888.79 hectars that represented by land unit 5 and 6 (in Pidpid village and Ababi in slopepersentage of 8 – 15 %;),7, 8 and 14 ((Abang and Kertamandala village in slope percentage 0 – 8 %),16 and 18 (Purwakerti and Biaslantang village) in slope percentage 8 – 15 %) about 1.888,79 hectarand 18, respecticvly Plant of Robusta coffee, Cocoa, Clove and Melinjo marginally suitable to bedeveloped area 2,690.44 hectars, represented by land unit 1and 4 (Datah village 15 – 40%); 10, 11and 12 (Tista village in slope percentage 15 – 40%), 19 and 20 (Labosari village 2 – 8 %) and 24(Bunutan village in slope percentage > 40%) to be area 2.690,44 hectars 1, 4, 10, 11, 12, 19, 20and 24.
Keywords: Land unit; Land characteristics; matching; land suitable